Pemanfaatan AI Dalam Dunia Game - Ahmad Padla Kamal; Febria Wardhani, Dyah (Jurnal Sintaks Logika, 2025)
The utilization of artificial intelligence (AI) in the gaming industry has significantly advanced, impacting gameplay experience, game development, and player interaction. This study analyzes AI applications in various aspects of the industry, including the development of non-player characters (NPCs), enhancement of gameplay realism, and optimization of game design, using literature review and analysis of modern implementations. The findings reveal that AI enhances NPC intelligence, enables more adaptive and challenging gameplay, and supports developers in procedural design and testing. Moreover, AI processes player data to deliver personalized and dynamic experiences. In conclusion, AI fosters innovation and efficiency in game development, though challenges such as balancing AI with player engagement and addressing ethical concerns in data usage must be considered for sustainable and responsible growth.